Synthesis of fulvene vinyl ethers by gold catalysis - Ahrens, Alexander; Schwarz, Julia; Lustosa, Danilo Machado; Pourkaveh, Raheleh; Hoffmann, Marvin; Rominger, Frank; Rudolph, Matthias; Dreuw, Andreas; Hashmi, A. Stephen K. (Chemistry - a European journal, 2020)
Abstract Gold-catalyzed cyclization of 1,5-diynes with ketones as reagents and solvent provides diversely substituted vinyl ethers under mild conditions. The regioselectivity of such gold-catalyzed cyclizations is usually controlled by the scaffold of the diyne. Herein, we report the first solvent-controlled switching of regioselectivity from a 6-endo-dig- to 5-endo-dig-cyclization in these transformations, providing fulvene derivatives. With respect to the functional-group tolerance, aryl fluorides, chlorides, bromides, and ethers are tolerated. Furthermore, the mechanism and selectivity are put to scrutiny by experimental studies and a thermodynamic analysis of the product. Additionally, 6-(vinyloxy)fulvenes are a hitherto unknown class of compounds. Their reactivity is briefly evaluated, to give insights into their potential applications.
Gesehen am 12.05.2020